Correlation of Academic Stress with Internet Addiction in Students Junior High School Class VIII (Observational Study at SMP Islam Al Azhar 14 Semarang) - Putri, Annafi Nandhira; Ayuningtyas, Putri Rokhima; Ratnawati, - (International Journal of Human and Health Sciences (IJHHS), 2024)
Academic stress is a situation where students are unable to meet academic demands and perceive these demands as a nuisance or threat. A person’s academic stress is influenced by one factor, namely internet addiction. This research aims to determine the relationship between academic stress and internet addiction in Class VIII Middle School Students. This research uses an analytical observational research design with a cross sectional approach. The research sample was taken using a proportional sampling technique, totaling 68 students in class VIII of Al Azhar Islamic Middle School 14 Semarang who met the inclusion criteria. The inclusion criteria were class VIII students who were willing to fill out the questionnaire completely. The questionnaires used were Gadzella’s Students Life Stress Inventory and Young’s Internet Addiction Test. Data analysis used Spearman correlation. In calculating internet addiction scores, the majority were found to be in the moderate category at 50 students (73.5%). In the academic stress score, it was found that the majority of academic stress was in the moderate category for 44 students (64.7%). The results obtained from the Spearman rho statistical test, r = 0.674 and p = 0.000 (p<0.05). There is a significant relationship between academic stress and internet addiction with a strong relationship. The direction of the positive relationship shows that the more academic stress, the more it will cause internet addiction. International Journal of Human and Health Sciences Vol. 08 No. 02 Apr’24 Page: 147-150